Znaczenie stopy odzysku w ocenie ryzyka kredytowego - Wójcicka, Aleksandra (The Significance of Recovery Rates in Credit Risk Estimation, 2007)
The new Basel Capital Accord permits the use of Internal-rate Based credit risk models, which allows more effective evaluation of Exposure at Default (EAD). Due to that fact banks can use their capitals more sufficiently and assess the price of given loans and probability of payment refusal. Models used nowadays significantly differ from one another when considering ways of obtaining probability of default (PD), recovery rates (RR), defining existing connections between PD and RR as well as the factors influencing the credit risk. This paper presents different approaches to RR evaluating in credit risk analysis. Significant differences in treating RR in various generations of models were described. The tendencies and directions of further research were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 266-276